Amphotericin B-conjugated biogenic silver nanoparticles as an innovative strategy for fungal infections. (October 2016) - Ahmad, Aftab; Wei, Yun; Syed, Fatima; Tahir, Kamran; Taj, Raheela; Khan, Arif Ullah; Hameed, Muhammad Usman; Yuan, Qipeng
Abstract: New strategies are required to improve the efficacy of drugs and to treat the emerging microbial resistance. An effective strategy is to combine drugs with metal nanoparticles for the control of microbial infections and resistance. Keeping in view this fact, we developed a facile and eco-friendly protocol for the synthesis of amphotericin B-conjugated silver nanoparticles and their assessment as an antifungal agent. Phytochemicals from the aqueous extract of Maytenus royleanus and amphotericin B were used as capping agents to prepare two types of silver nanoparticles i.e. (i) biogenic silver nanoparticles (b-AgNPs) and (ii) amphotericin B-conjugated biogenic silver nanoparticles (Amp-bAgNPs). UV-Vis spectroscopy was used to detect the characteristic surface Plasmon resonance peaks (SPR) for the prepared nanoparticles (424–433 nm). High-resolution transmission electron microscopy (HRTEM) study revealed the formation of well dispersed and spherical silver nanoparticles and Amp-bAgNPs with an average particles size of 10 and 15 nm. EDX and FTIR studies confirmed the elemental composition and surface adhered biomolecules in the prepared nanoparticles respectively. Biogenic silver nanoparticles revealed low to moderate antifungal activity (4–8 mm ± 0.2), however, the amphotericin B conjugated silver nanoparticles exhibited significant activity against Candida albicans (16 mm ± 1.4) and Candida tropicalis (18 mm ± 1.5). In conclusion, the enhanced antifungal activity of the Amp-AgNPs conjugate system is due to the synergy between the antifungal activity of amphotericin B and the antimicrobial property of silver. The findings of this study suggest that the conjugated nanoparticles could be used as efficient antifungal agents and drug delivery vehicles. Furthermore, this is the first report describing the synthesis of silver nanoparticles using the aqueous extract of Maytenus royleanus and the conjugation of amphotericin B, an antifungal drug, to the phytosynthesized silver nanoparticles. Highlights: Preparation of biogenic silver nanoparticles. Covalent conjugation of amphotericin B to biogenic nanoparticles. Enhanced antifungal activity. A novel green approach to treat fungal infections.